Migration and fate of characteristic pollutants migration from an abandoned tannery in soil and groundwater by experiment and numerical simulation. (May 2021) - Guo, Shan-shan; Wu, Hao; Tian, Yong-qiang; Chen, He-xiao; Wang, Yu; Yang, Jin-yan
Abstract: The tannery industry is an integral part of economic development in many developing countries, and the environmental pollution caused by the tannery industry cannot be ignored. In this study, soil and groundwater samples at different depths were collected from an abandoned tannery to investigate the temporal and spatial distribution of characteristic pollutants produced by tanning. The concentrations of Cr, Cl, F and NH4 + –N in the soil from the sludge temporary storage area were higher than those from the liming and unhairing workshop, chrome tanning workshop, wastewater outlet, and around wastewater pond. The concentration of Cr(VI) in all sampling sites was below the detection limit. The main species of Cr in the groundwater were Cr(NH3 )6 Cl 2+ and CrO4 2− based on the simulation of Visual MINTEQ. The saturation index was negative and changed with time indicating that Cr existed in the dissolved phase. The proportion of Cr(VI) to total Cr was negatively correlated with the saturation index in village 1 and village 3. The simulation results from Visual MODFLOW and MT3DMS showed that the migration of Cr, NH4 + –N, Cl − and F − mainly occurred in the Quaternary system. The coverage of the pollution plume of pollutants in villages 1 and 3 was as follows: Cr > NH4 + −N > Cl − > F − . Two decay rate calculation methods of pollutants with migration time and distance were put forward to provide a basis for the actual investigation of the pollution migration scope and time determination. Graphical abstract: Image 1 Highlights: The migration of Cr, NH4 + –N, F − and Cl − mainly occurred in the Quaternary system. The saturation index of Cr increased firstly and then stabled or declined. The species of Cr in groundwater were mainly Cr(NH3 )6 Cl 2+ and CrO4 2− . Two calculation methods of decay rate considering the actual situation were given.